2011
DOI: 10.1111/j.1467-8551.2011.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Opening Strategy: Evolution of a Precarious Profession

Abstract: International audienceThis paper takes the long view on the development of strategy as a profession, from the 1950s to today. We identify strategy as a structurally precarious profession, subject to cyclical demand and shifts in organizational power. This precariousness has increased with the secular shift towards more open forms of strategy-making, with more transparency inside and outside organizations and more inclusion of different actors internally and externally. We analyse four forces - organizational, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
490
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(548 citation statements)
references
References 60 publications
(56 reference statements)
9
490
1
9
Order By: Relevance
“…Effectively excluding individuals from these practices can be difficult to justify, especially in modern times of increasing transparency and 'open strategy' in contexts beyond the public sector (Whittington, Cailluet, & Yakis-Douglas, 2011). Both coordination costs and scrutiny associated with these 'interesting' practices are consequently high.…”
Section: Sub-process B: the Distribution Of Interests Shapes Coordinamentioning
confidence: 99%
See 1 more Smart Citation
“…Effectively excluding individuals from these practices can be difficult to justify, especially in modern times of increasing transparency and 'open strategy' in contexts beyond the public sector (Whittington, Cailluet, & Yakis-Douglas, 2011). Both coordination costs and scrutiny associated with these 'interesting' practices are consequently high.…”
Section: Sub-process B: the Distribution Of Interests Shapes Coordinamentioning
confidence: 99%
“…Not every strategic change initiative involves the opening of strategy (cf. Whittington et al, 2011) to individuals or groups who have the ability to pursue their own interests. In other settings participation may be more effectively restricted, thereby limiting coordination costs.…”
Section: Practical Implications Limitations and Future Researchmentioning
confidence: 99%
“…Tying the notion of open strategy to that of open innovation, Chesbrough and Appleyard argued that open strategy "balances the tenets of traditional business strategy with the promise of open innovation" (Chesbrough and Appleyard 2007, p. 58). Similarly, in their assessment of the concept of open strategy, Whittington et al (2011) suggested that open strategy challenges traditionally exclusive approaches (see also Hautz et al 2017). In their definition of open strategy, Whittington et al (2011, p. 534) went so far as to argue that "open innovation is a subset of open strategy: innovation is just one of many kinds of strategy process increasingly subject to openness".…”
Section: Even Trott and Hartmann Themselves Acknowledge That "The Dicmentioning
confidence: 99%
“…Consequently, middle managers are now more often recognized as key stakeholders in the process, and it is argued that their participation in the formulation of strategies increases their commitment (Barton and Ambrosini, 2013). The openness of SP therefore most commonly refers to the communication of strategies, once they are formulated (Whittington et al, 2011). In HK, deployment and catch-balling are concepts that point to a different and somewhat challenging direction.…”
Section: Domentioning
confidence: 99%
“…Kenyon (2000in Jolayemi 2008, describe the practice as: Overall objectives (vision, long-term objectives) are set at the top and are then interpreted in dialogue with members of the organization. The ultimate aim is that all layers of employees are invited to work on their own objectives in connection to the overall ones (Lee and Dale 1998;Jolayemi, 2008 (Whittington et al, 2011) and the original idea of implementation as a close-ended and converging process has been balanced with a view that involves more integration, communication, and coordination (Okumus, 2003;Wolf and Floyd, 2013). Consequently, middle managers are now more often recognized as key stakeholders in the process, and it is argued that their participation in the formulation of strategies increases their commitment (Barton and Ambrosini, 2013).…”
Section: Domentioning
confidence: 99%